El método analítico como método natural (2010)
ABSTRACT: Based on the definition of analysis like the decomposition of a whole in its constituent elements to proceed to its understanding and re-articulation, this paper expound the analytical method like the natural method of the human being, show its relationships with the scientific method, and make explicit its intimate entailment with ethic, that is an habit that results of the incorporation of the method.